Lamotrigine (Sazar) in the treatment of epilepsy: four years of experience in Svt. Luka's Association of Medical institutions for the Diagnosis, Treatment, and Rehabilitation of Nervous System Diseases and Epilepsy - K. Yu. Mukhin; O. A. Pylaeva; M. Yu. Bobylova; N. V. Freydkova (Русский журнал детской неврологии)
Aim. To assess the efficacy and tolerability of lamotrigine (Sazar) for various forms of epilepsy, based on long-term experience of Svt. Luka's Association of Medical Institutions for the Diagnosis, Treatment, and Rehabilitation of Nervous System Diseases and Epilepsy. We analyzed the data obtained during 4 years (from June 2018 to August 2022).Materials and methods. We evaluated the efficacy and tolerability of Sazar in 104 patients aged 3 to 37 years (87 children and 17 adults (12 women and 5 men)); their mean age was 9.7 years. The sample included 42 males and 62 females. All of them were treated at Svt. Luka's Association of Medical Institutions for the Diagnosis, Treatment, and Rehabilitation of Nervous System Diseases and Epilepsy.The sample included patients with structural and presumably structural focal epilepsy (n = 44), focal epilepsy of unknown etiology (n = 6), genetic and presumably genetic epilepsy and epileptic encephalopathies (n = 43), idiopathic epilepsy (n = 11).Sazar was used as a monotherapy in 38 patients, whereas 66 patients received it in combination with other antiepileptic drugs (AED) (Sazar + 1 AED in 48 patients; Sazar + 2 AED in 18 patients). Two patients initially receiving polytherapy were successfully transferred to Sazar monotherapy.The dose of Sazar varied between 75 and 400 mg/day. In the majority of patients, including all children, Sazar daily dose was split into 2 portions. Three adult patients received Cazar once a day either in the evening (n = 2) or in the morning (n = 1) at a dose of 200 mg/day. The follow-up time was between 6 months and over 4 years.Results and conclusion. Therapeutic remission was achieved in 47 out of 104 patients (45.2 %) receiving Sazar. As many as 35 patients (33.6 %) demonstrated an at least 50 % reduction in seizure frequency; 22 patients had no effect (21.2 %). None of the participants developed significant aggravation.Only 9 patients (8.6 %) discontinued Caser due to its initial low efficacy, while another 8 patients (7.6 %) stopped to receive Casar because it became ineffective after 6–12 months of treatment. In general, good therapeutic effect (remission or at least 50 % reduction in seizure frequency) was achieved in 82 out of 104 patients (78.8 %). Given the fact that this study included patients with severe epilepsy, we can conclude that treatment was very effective.Casar was most effective in patients with focal epilepsy (including structural, presumably structural, structural-genetic, and that of unidentified etiology) and idiopathic generalized epilepsy.The majority of the patients (n = 94; 90.4 %) demonstrated good tolerability of Casar. Casar-associated side effects were registered in 10 patients (9.6 %). Allergic skin rash was observed in 5 cases (4.8 %) and developed during the first 2 months of therapy. Allergic reactions accounted for 50 % of all side effects and were the only reason for Casar discontinuation due to poor tolerability.Two female patients of reproductive age started Sazar to reduce the valproate dose that caused severe menstrual disorders, weight gain, alopecia, and edema. Halving the dose of valproate (up to 750 mg/day) in combination with Casar significantly improved treatment tolerance. One patient gave birth to a healthy baby when she was receiving monotherapy with Sazar at a dose of 350 mg/day.Eight patients receiving Sazar reported a significant improvement in their mood and behavior (one patient that had earlier been diagnosed with depression discontinued antidepressants after Sazar initiation since she did not need them any longer). None of the patients reported any negative effects of Sazar on their memory, attention, mood, and behavior (as evaluated by patients and parents; in some cases, by a neuropsychologist).Patients’ adherence to treatment confirmed high Sazar efficacy and tolerability: 82 out of 104 patients (78.8 %) continued to receive the drug after 6 months of treatment and 69 patients (66.3 %) still continued it after 12 months of treatment. The follow-up period varied between 6 months and 4 years.Thus, our findings suggest high efficacy and good tolerability of long-term therapy with Sazar in patients with different forms of epilepsy.